Hubungan Tingkat Pengetahuan Diet DiabetesMelitus Terhadap Asupan Serat Pasien DiabetesMelitus Rawat Jalan Di Rsud Kota Surakarta - Syam, Nurnyingsih; , Elida Soviana, S.Gz., M.Gizi; , dr. Listiana Darmawati, M.Si (2016)
Introduction: The proportion of diabetes melitus patients in Hospital of Surakarta is high at approximately 7,15%. Knowledge is one of factors that can help the patients in carrying out the process of dealing with DM. Knowledge about DM diet will affect attitudes in order to form the appropriate dietary behavior. With DM diet by consuming adequate intake of fiber can help to control blood glucose levels. Objective: To determine the relationship between knowledge about DM diet and intake of fiber in diabetes mellitus outpatients at Hospital of Surakarta Methods: This observational research used cross-sectional design with number of subjects was 37 patients, whom were obtained using consecutive sampling methods. Knowledge level about DM diet were obtained through an interview using a questionnaire on knowledge about DM diet, while fiber intake data were obtained through an interview using a semi-quantitatif food frequency questionnaire. Statistical analysis used Rank Spearman tests. Results: The medians value of level of knowledge about DM diet was 63.0%, with minimum value was 13% and maximum value was 58.41%, while the median intake of fiber was 9.30 g/day with minimum value was 3.48 g/day and maximum value was 26.82 g/day. Of the 19 subjects who had sufficient knowledge, 94.7% of them consumed fiber less than 25 g/day and only 2.7% who had sufficient intake of fiber. All subject who had poor knowledge about DM diet had low intake of fiber and one subject who had a good knowledge about DM diet also had low fiber intake. Rank Spearman statistical analysis showed that there was no relationship between the level of knowledge about DM diet and fiber intake (p = 0.272). Conclusion: There was no relationship between the level of knowledge about DM diet and fiber intake in diabetic outpatients at Hospital of Surakarta